Growth induced by the One Belt and One Road initiative - Gao, Fan (2017)
This paper uses trade openness ratio to study the relationship between trade openness and economic growth for a sample of China during 2010-2016, and the aim of this paper is to find the role of the One Belt and One Road initiative in China’s economic growth. This dissertation examines the role of the One Belt and One Road initiative in China’s economic growth within the framework of endogenous growth. Specifically, I analyze the statistics of openness and economic growth from China during 2010-2016. The findings of this study provide empirical evidence supporting the hypothesis that higher trade openness stimulates faster China’s economic growth. However, in the research period, the One Belt and One Road initiative not stimulates China’s economic growth increasing fast, it indeed has a strong effect on China’s economic growth. Thus, this paper suggests China and countries along with the One Belt and One Road initiative to increase openness to trade through economic reform, and improving manufacturing industry restructuring and upgrading and promoting global cooperation on production capacity to increase economic growth.